ICT Systems Security and Privacy Protection: 30th IFIP TC 11 International Conference, SEC 2015, Hamburg, Germany, May 26-28, 2015, Proceedings - Federrath, Hannes; Gollmann, Dieter (ICT Systems Security and Privacy Protection 30th IFIP TC 11 International Conference, SEC 2015, Hamburg, Germany, May 26-28, 2015, Proceedings, 2015)
This book constitutes the refereed proceedings of the 30th IFIP TC 11 International Information Security and Privacy Conference, SEC 2015, held in Hamburg, Germany, in May 2015.The 42 revised full papers presented were carefully reviewed and selected from 212 submissions.